Pengaruh Lama Fermentasi Terhadap Karakteristik Fisik, Kimia, dan Organoleptik Nata De Leri dengan Penambahan Sari Kulit Buah Naga Merah (Hylocereus polyrhizus) - Sherin Gratia Arvenia Latongki; Christine F. Mamuaja; Jolanda C. E. Lamaega; Lucia C. Mandey; Yoakhim Y. E. Oessoe; Riel J. J. Umboh (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2026)
This study aimed to determine the effect of different fermentation durations (6, 8, 10, and 12 days) on the physical and chemical characteristics as well as the panelists’ preference levels of Nata De Leri fortified with red dragon fruit peel extract as a natural colorant. A Completely Randomized Design (CRD) was applied with four treatments and three replications. The tested parameters included thickness, texture, color, weight, moisture content, crude fiber content, and organoleptic attributes (color, aroma, taste, texture) evaluated by 25 panelists. The results showed that fermentation duration significantly affected the thickness, texture, color, and weight of nata. Thickness increased from 2.8 to 12.4 mm, texture from 0.16 to 7.75 N, and weight from 163.3 to 436.0 g. Moisture content and crude fiber also increased as fermentation progressed. The addition of red dragon fruit peel extract influenced the color of the nata, particularly by enhancing the redness intensity (a* value). Organoleptic testing indicated that the 12-day fermentation treatment received the highest scores for all sensory attributes, although the sour aroma and distinctive taste derived from phenolic compounds in dragon fruit peel resulted in panelist scores ranging from slightly dislike to neutral. Overall, 12 days of fermentation produced nata with the best physical, chemical, and sensory characteristics.